The apologie, or defence of a verity heretofore published concerning a medicine called aurum potabile, that is, the pure substance of gold, prepared, and made potable and medicinable without corrosiues, helpfully giuen for the health of man in most diseases, but especially auaileable for the strenghning [sic] and comforting of the heart and vitall spirits the perfomers of health: as an vniversall medicine. Together with the plaine, and true reasons ... confirming the vniversalitie thereof. And lastly, the manner and order of administration or vse of this medicine in sundrie infirmities. / By Francis Anthonie of London, doctor in physicke. [electronic resource] : (1616)
Summary goes here